УПРАВЛЕНИЕ ПОТОКАМИ АКТИВНОЙ И РЕАКТИВНОЙ МОЩНОСТЕЙ В ЭЛЕКТРИЧЕСКИХ СЕТЯХ - Говоров, Ф.П.; Говоров, В.Ф. (Інститут електродинаміки НАН України, Київ, 2016)
Management issues of voltage, reactive and active power modes in distribution networks through the use of booster transformers (BT) are considered. A mathematical model of the processes in a quasi-steady-electromagnets modes of urban electrical networks with BT is developed. The possibility of power flow control in such networks by using phase shifting transformers is established. It is shown that for different groups of windings connection BT takes place more power consumption from the mains or its recovery from the load to the supply network, because it provides a shift of the load current in the direction of lag or lead. In this case for some connection groups an increase in voltage across the load is observed, but for other groups – reduction. References 3, figures 2.